Scholarly Black Market - Sorooshian, Shahryar (Springer Netherlands, 2017)
Fake and unethical publishers’ activities are known by most of the readers of Science and Engineering Ethics. This letter tries to draw the readers’ attention to the hidden side of some of these publishers’ business. Here the black market of scholarly articles, which negatively affects the validity and reliability of research in higher education, as well as science and engineering, will be introduced.